Genes-environment relations of one-carbons metabolism determinants and their associations with pathology in West Africa - (:unkn) unknown (My University, 2009)
In this work we had analysed nutritional and genetics determinants involved in homocysteine metabolism according to geographical areas, environment-gene interactions and their association with the most prevalent diseases in West Africa, viral B hepatitis, malaria and metabolic syndrome linked to obesity. We had shown that MTHFR 677C>T polymorphism had a dramatic influence on homocysteinemia, in relation with folates deficit. Folates status was associated with MTHFR 677T allelic frecuency, when comparing populations worldwide. There was not migrational influence, when African populations were compared with those from North America. We had found an association between T allele and favourable evolution of viral B hepatitis in Africa. In the other hand, we observed no influence of TCN776C>G on homocysteinemia. When comparing TCN 776C>G polymorphism in migrant and autochthonous populations, our results suggested a selection pressure related to malaria. This polymorphism was associated with the severe form of malaria fever. Influence of homocysteine determinants on clinical and biological markers of metabolic syndrome in Africa was preferably observed in women, with a significant association with ApoA and HDL.
Keywords: African Research